Development of Formalin Tester Device for Food Using Microcontroller AT89S51 - Iswanto Iswanto; Prisma Megantoro; Nia Maharani Raharja (Proceeding of the Electrical Engineering Computer Science and Informatics, 2020)
This article discusses the manufacture of formaldehyde content test kit device. The device made can find out whether formalin or samples that are dropped are reagents, its characteristics can be processed electronically to determine the levels of formalin detected in the reagent/test kit. The design is made using AT89S51 microcontroller. Detection of formaldehyde levels using a color measurement method for reagent fluids consisting of R, G, and B values. Measurement of these color parameters using the TCS230 sensor. With this device, it is expected to facilitate health workers, especially health analysts, to automatically test the level of formaldehyde in food with a display on the LCD. The result of device test, this device is feasible to use by the percent error value of less than 10%.